2016
DOI: 10.14257/ijmue.2016.11.8.34
|View full text |Cite
|
Sign up to set email alerts
|

Research on Nonlinear Thinking of Landscape Architecture Design based on Computer-aided Parametric Model

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…e parametric illustration is a dynamic process and a logical construction process, which provides an open design method for landscape garden design. Literature [27] reveals the historical evolution process of natural concepts by analyzing the philosophical background of parameterization, pointing out that parameterization is an inevitable product that adapts to the conditions of today's technology and productivity. Parametric design is to construct logic and finally solve design problems, which is also in line with the natural development trend.…”
Section: Related Workmentioning
confidence: 99%
“…e parametric illustration is a dynamic process and a logical construction process, which provides an open design method for landscape garden design. Literature [27] reveals the historical evolution process of natural concepts by analyzing the philosophical background of parameterization, pointing out that parameterization is an inevitable product that adapts to the conditions of today's technology and productivity. Parametric design is to construct logic and finally solve design problems, which is also in line with the natural development trend.…”
Section: Related Workmentioning
confidence: 99%
“…City parks are more than just botanical landscapes. It is also a reflection of the ecological functions of the entire plant community and forest community landscape [9,10]. The construction of urban forest is not only reflected in the improvement of the urban appearance.…”
Section: Construction Of Landscape Architecture In Residentialmentioning
confidence: 99%
“…According to Table 3, after changing the reliability of the data source e, although the evidence function's support for fact "1" is reduced, S( 1) is still greater than the sum, and Bel(1) is still greater than 0.9. From this, it is concluded that when the evidence is the same, even if the weight adjustment conflicts, the final conclusion is still close to the actual situation [27]. It can be seen that, based on the data fusion algorithm, we can also know that regional cultural elements are becoming more and more important for landscape architectural design.…”
Section: Results and Analysis Of Data Fusion Algorithmmentioning
confidence: 58%